Integrated collaborative building design using Internet technology - Roshani, D.M.R. (2005)
Communication between the parties in a project of an integrated collaborative engineering system has been the subject of active research for many years. The construction industry has a long tradition of collaborative working between the members of the construction team. At the design stage, this has traditionally been based on physical meetings between representatives of the principal design team members. To aid these meetings, the information and communication technologies that are currently available have been used.